Encapsulation of octadecane in poly(divinylbenzene-co-methyl methacrylate) using phase inversion emulsification for droplet generation. Issue 1 (2nd January 2016) - Namwong, Siriluk; Islam, Md. Zahidul; Noppalit, Sayrung; Tangboriboonrat, Pramuan; Chaiyasat, Preeyaporn; Chaiyasat, Amorn
Abstract: Octadecane (OD), a heat storage material, was encapsulated into poly(divinylbenzene- co -methyl methacrylate) or P(DVB- co -MMA) matrix via the microsuspension polymerization. The oil droplets were first generated by using the phase inversion emulsification, i.e., adding a sodium dodecyl sulphate (SDS) aqueous solution into an oil phase (monomers:OD = 1:1) containing various concentrations of poly(vinyl alcohol) (PVA). Results showed that 0.1 wt% of SDS in aqueous medium with the additional rate of 2 mL/min and 3 wt% of PVA in oil phase were the optimal conditions for the formation of nonspherical microcapsules. The smallest number- ( dn ) and weight- ( d w ) average diameters of P(DVB- co -MMA)/OD were, respectively, 3.1 and 3.2 µm with a narrow particle size distribution ( d w / d n ) of 1.02. The latent heats of the encapsulated OD increased with increasing MMA content of microcapsules. The heat of melting (Δ H m ; 223 J/g-OD) and crystallization (Δ H c ; 230 J/g-OD) of the OD encapsulated in microcapsules using DVB:MMA of 30:70 were higher than those using only PDVB (189 and 193 J g-OD for Δ H m and Δ H c, respectively) and comparable to those of bulk OD (233 and 234 J/g-OD for Δ H m and Δ H c, respectively). The obtained P(DVB- co -MMA)/OD microcapsules would be useful as high performance heat storage material.